The effectiveness of biology education research textbooks to train students' critical thinking skills - Finda Vericha Ngenda; Muhammad Zaini; Yudi Firmanul Arifin (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The Biology Education Research (BER) course in the 6th semester of S1 Biology Education FKIP Lambung Mangkurat University, discusses research methodology which includes types of research, methods, variables, theoretical foundations, and hypotheses. However, textbooks that are in accordance with the Semester Learning Plan (LP) and can develop students' critical thinking skills are needed. Based on these problems, the textbook is prepared in accordance with the textbook components in general and develops textbooks based on the State of The Art (SOTA) concept, namely renewal in improving cognitive understanding and obtaining the results of critical thinking by containing exercises in the form of questions based on Bloom's taxonomy ranging from C3-C5. This study aims to produce textbooks on BER that are effective to use and can train students' critical thinking skills. This type of research uses the Education Design Research (EDR) model through the Tessmer Formative Test. Testing the effectiveness of the textbook on BER was carried out to a small group evaluation totaling five students and a field test totaling 25 students. The test uses instruments in the form of working on evaluation questions and college student activity sheets (CSAS). The results of the study based on the expected effectiveness test of the textbook developed with an average value of 69.20 increased to 81.70. While the actual effectiveness tests got an average value of 71.36 increasing to 85.36. Then the average N-gain value is 0.5 which is in the moderate category. These results prove that the BER textbook is effective in learning.Abstrak. Mata kuliah Penelitian Pendidikan Biologi (P2BIO) pada semester 6 S1 Pendidikan Biologi FKIP Universitas Lambung Mangkurat, membahas metodologi penelitian yang meliputi jenis penelitian, metode, variabel, landasan teori, dan hipotesis. Namun, buku ajar yang sesuai dengan Rancangan Pembelajaran Semester (RPS) dan dapat mengembangkan keterampilan berpikir kritis mahasiswa diperlukan. Berdasarkan permasalahan tersebut, buku ajar tersebut disusun sesuai dengan komponen buku ajar pada umumnya dan mengembangkan buku ajar berdasarkan konsep State of The Art (SOTA) yaitu pembaharuan dalam meningkatkan pemahaman kognitif dan memperoleh hasil cara berpikir kritis dengan memuat latihan berupa pertanyaan-pertanyaan berdasarkan taksonomi bloom mulai dari C3–C5. Penelitian ini bertujuan untuk menghasilkan buku ajar tentang P2BIO yang efektif digunakan dan dapat melatihkan keterampilan berpikir kritis mahasiswa.  Jenis penelitian ini menggunakan model Education Design Research (EDR) melalui Uji Formatif Tessmer. Pengujian keefektifan buku ajar tentang P2BIO tersebut dilakukan kepada kelompok kecil (small group evaluation) berjumlah lima mahasiswa dan uji lapangan (field test) berjumlah 25 mahasiswa. Pengujian tersebut dengan menggunakan instrumen berupa pengerjaan soal evaluasi dan lembar kegiatan mahasiswa (LKM). Hasil penelitian berdasarkan uji keefektifan harapan terhadap buku ajar yang dikembangkan dengan nilai rata-rata 69,20 meningkat menjadi 81,70. Sedangkan uji keefektifan aktual mendapatkan nilai rata-rata 71,36 meningkat menjadi 85,36. Maka nila rata-rata N-gain sebesar 0,5 yang berada pada kategori sedang. Hasil ini membuktikan buku ajar BER tersebut efektif dilaksanakan dalam pembelajaran.